Bioethics and social reality - Häyry, Matti; Takala, Tuija, 1971-; Herissone-Kelly, Peter (Value inquiry book series, 2005)
This book explores the many connections that bioethical thinking has with social reality. Bioethics, if it is to be effective, must engage with and address the actualities of modern life: policies, regulations, markets, opinions, and technological advances. In these original contributions fifteen notable scholars working in the North West of England take on this challenge. Values in Bioethics (ViB) makes available original philosophical books in all areas of bioethics, including medical and nursing ethics, health care ethics, research ethics, environmental ethics, and global bioethics.